Maternal High-Sucrose Diet Affects Phenotype Outcome in Adult Male Offspring: Role of Zbtb16 - Školníková, Elena; Šedová, Lucie; Chylíková, Blanka; Kábelová, Adéla; Liška, František; Šeda, Ondřej (Frontiers in Genetics, 2020)
Overnutrition in pregnancy and lactation affects fetal and early postnatal development, which can result in metabolic disorders in adulthood. We tested a hypothesis that variation of the Zbtb16 gene, a significant energy metabolism regulator, modulates the effect of maternal high-sucrose diet (HSD) on metabolic and transcriptomic profiles of the offspring. We used the spontaneously hypertensive rat (SHR) strain and a minimal congenic rat strain SHR-Zbtb16, carrying the Zbtb16 gene allele originating from the PD/Cub rat, a metabolic syndrome model. 16-week-old SHR and SHR-Zbtb16 rat dams were fed either standard diet (control groups) or a high-sucrose diet (HSD, 70% calories as sucrose) during pregnancy and four weeks of lactation. In dams of both strains, we observed an HSD-induced increase of cholesterol and triacylglycerol concentrations in VLDL particles and a decrease of cholesterol and triacylglycerols content in medium to very small LDL particles. In male offspring, exposure to maternal HSD substantially increased brown fat weight in both strains, decreased triglycerides in LDL particles, and impaired glucose tolerance exclusively in SHR. The transcriptome assessment revealed networks of transcripts reflecting the shifts induced by maternal HSD with major nodes including mir-126, Hsd11b1 in the brown adipose tissue, Pcsk9, Nr0b2 in the liver and Hsd11b1, Slc2a4 in white adipose tissue. In summary, maternal HSD feeding during pregnancy and lactation affected brown fat deposition and lipid metabolism in adult male offspring and induced major transcriptome shifts in liver, white, and brown adipose tissues. The Zbtb16 variation present in the SHR-Zbtb16 led to several strain-specificeffects of the maternal HSD, particularly the transcriptomic profile shifts of the adult male offspring.